Letter (copy) - Citrine, Walter, 1887-1983
011-0005-001 WMC/WJB/AC/300. International. 31st December, 1937 Sr. D. Pascual Tomas. El Diputado a Cortes por la Provincia de Murcia, VALENCIA, SPAIN. Dear Comrade Tomas, I thank you sincerely for your greetings and your good wishes, which I most heartily reciprocate. It is with joy that my colleagues and I learned of the recent successes of the Spanish workers who are fighting the Fascist forces. Our earnest wish is that success may continue to crown your efforts. You can rely upon the British Trade Union and Labour Movement doing all within its power to help you in this great struggle for liberty, which we recognise concerns not only the workers in your country, but the working classes of the whole world. With the Compliments of the Season, Yours faithfully, General Secretary. 292/946/11/5